The forecasting potential of adaptive models in tourism - Aleksandrova, Anna; Aigina, Ekaterina; Dombrovskaya, Veronika (Turyzm/Tourism, 2021)
The article discusses forecasting as one of the special scientific research areas which contribute to the assessment of tourist activity development prospects, the identification of key tourism development factors and effective management decision criteria. The study provides an overview of modern research methods used in Russia and other countries for making forecasts in the field of tourism. It aims at assessing the predictive capabilities of adaptive modeling, not frequently used currently in tourism research, for the quantitative analysis of tourist flows using the example of Barcelona, a major urban tourist destination in the pre-pandemic period. An example of a forecast for tourist numbers based on adaptive models is proposed, one of the key indicators showing tourist region success which have proven successful in the study of processes with a dynamic but unstable character.